THE EFFECT OF TUTORING FOR NATIONAL EXAM PREPARATION TOWARDS TRY OUT'S SCORE BY DRILL AND PRACTICE METHOD AT MAN PAKEM - Lina (Pendidikan Kimia Unimus, 2016)
Having study on private or class tutoring besides mainstream schools has been commonly done by students. From that fact, this research was conducted to know the effect of tutoring for national exam preparation towards students' achievement which showed by Try Out's scores of students at MAN Pakem, Sleman, Yogyakarta. The turoring was carried out by drill and practice method on chemistry subject. The hypotheses were test by paired T-test, since the data were normal. From the analysis data, it was found that the tutoring increased try out's scores of students at MAN Pakem, significantly.